2010
DOI: 10.1007/s00167-010-1256-4
|View full text |Cite
|
Sign up to set email alerts
|

High tibial valgus osteotomy in unicompartmental medial osteoarthritis of the knee: a retrospective follow-up study over 13–21 years

Abstract: Open and closing wedge high tibial osteotomies are a successful choice of treatment for unicompartmental degenerative diseases with associated varus in active patients. Survival of both techniques is comparable in our series and is associated with low pain scores, high satisfaction and high activity levels of the survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 37 publications
7
106
2
3
Order By: Relevance
“…The median follow up was 16.5 years (interquartile range (IQR) 14.5-17.9 years) satisfaction index was 80% (IQR 63-89), median knee injury and osteoarthritis outcome score was 71 (IQR 49-82) and median Western Ontario and McMaster university osteoarthritis index was 82 . There was no difference in survival rates or outcome scores when HTMOWO was compared to HTLCWO in this study but once again the study was likely underpowered to show any potential difference with fewer patients in the former group compared to the latter (Schallberger 2011).…”
Section: Wwwintechopencommentioning
confidence: 74%
“…The median follow up was 16.5 years (interquartile range (IQR) 14.5-17.9 years) satisfaction index was 80% (IQR 63-89), median knee injury and osteoarthritis outcome score was 71 (IQR 49-82) and median Western Ontario and McMaster university osteoarthritis index was 82 . There was no difference in survival rates or outcome scores when HTMOWO was compared to HTLCWO in this study but once again the study was likely underpowered to show any potential difference with fewer patients in the former group compared to the latter (Schallberger 2011).…”
Section: Wwwintechopencommentioning
confidence: 74%
“…Schallberger et al 17 found that survival of open-as well as closed-wedge osteotomy was comparable in their series. It was associated with low pain scores, high satisfaction and high activity levels of the survivors.…”
Section: Discussionmentioning
confidence: 86%
“…Encouraging results thus far have been seen, however, with improvements seen in visual analog scale, Knee Injury and Osteoarthritis Outcome Score, and Western Ontario and McMaster Universities Osteoarthritis Index scores, and only slight progression of osteoarthritis in the affected compartment. 6 This technical note presents a technique for a safe and efficient surgical procedure using the Arthrex iBalance system (Arthrex). This system offers an accurate and reproducible mechanism to ensure correct biplanar alignment for opening-wedge osteotomies, while offering certain advantages such as less hardware prominence and irritation, requiring hardware removal.…”
Section: Discussionmentioning
confidence: 99%